A NON-EXISTENT NEW TESTAMENT. ON THE CONFESSIONAL ASPECTS OF JAN KOCHANOWSKI’S RELIGIOUS POETRY - Rusnak, Radosław (Prace Polonistyczne, 2021)
The article lists all references to the New Testament characters, like Jesus Christ, Saint Peter, and Lazarus, in Jan Kochanowski’s works. To some of them additional commentaries are given, e.g. to Elegy I 10 (from the collection Elegiarum libri duo) where the scene of the betrayal of Judas is used as a warning to the bellicose pope Paul IV who intended to regain Naples. The article also points to the fragments where the presence of Christ may be seen as desirable or even necessary and yet he is conspicuous by his absence. This particularly applies to Laments, as the collection completely ignores the Christian perspective on the redemptive power of suffering. Given the scarcity of references to the New Testament in Jan Kochanowski’s works, which is even more striking when compared to the multiple references that they make to David’s psalms, the article speculates on the reasons for Kochanowski’s preferences as well as opens a broader discussion on the confessional aspects of Kochanowski’s poetry.